2022
DOI: 10.1177/15598276221087624
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions to Treat Type 2 Diabetes in Adults with a Goal of Remission: An Expert Consensus Statement from the American College of Lifestyle Medicine

Abstract: Objective: The objective of this Expert Consensus Statement is to assist clinicians in achieving remission of type 2 diabetes (T2D) in adults using diet as a primary intervention. Evidence-informed statements agreed upon by a multi-disciplinary panel of expert healthcare professionals were used. Methods: Panel members with expertise in diabetes treatment, research, and remission followed an established methodology for developing consensus statements using a modified Delphi process. A search strategist systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 101 publications
(176 reference statements)
1
32
0
4
Order By: Relevance
“…In line with the hypothesis, the duration of interventions could be impact in the results and mostly should be > six months to observe favorable changes in T2DM [ 68 ]. In our study, we found that the duration of the interventions was, on average, mostly one year.…”
Section: Discussionmentioning
confidence: 81%
“…In line with the hypothesis, the duration of interventions could be impact in the results and mostly should be > six months to observe favorable changes in T2DM [ 68 ]. In our study, we found that the duration of the interventions was, on average, mostly one year.…”
Section: Discussionmentioning
confidence: 81%
“…Zudem gelang bei der Hälfte der Teilnehmer, die zusätzlich eine Formuladiät erhielten, die Konversion von einem Prädiabetes in eine Normoglykämie, während dies bei weniger als einem Drittel der ausschließlich mit einer Lebensstilintervention behandelten Teilnehmer der Fall war [115]. Aus den genannten Gründen sehen Fachgesellschaften eine Remission sogar als primäres Behandlungszie an [116].…”
Section: Ddg-praxisempfehlungunclassified
“…This large discrepancy between a proportion of patients who met the POC and TOC may due to the nature of diabetes, financial burden, work and environment related factors. Recent statement from the American College of Lifestyle Medicine suggested that an ability of diabetes control or even diabetes remission is related to its intensity of preventive interventions [11]. Therefore, it is explainable that this result will help us drive the healthcare system that we then need to use our data to implement more intense interventions with patients to improve TOC indicators.…”
Section: Discussionmentioning
confidence: 99%
“…This provides free health care at the point of service in order to guarantee access to essential health care at primary care units (PCUs) [10]. Moreover, a resilient health system and management support team are a fundamental tenet of the diabetes care model linked to improved outcomes of diabetes control [11]. Services include health promotion, education, and screening for risk factors that lead to diabetes complications driven by interdisciplinary collaboration, proactive policies, and holistic care approaches [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation